2015
DOI: 10.18632/oncotarget.5751
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pentacyclic triterpenes found inPerilla frutescensfor inhibition of skin tumor promotion by 12-O-tetradecanoylphorbol-13-acetate

Abstract: A series of pentacyclic tritperpenes found in Perilla frutescens (P. frutescens), including ursolic acid (UA), oleanolic acid (OA), corosolic acid (CA), 3-epi-corosolic acid (3-epiCA), maslinic acid (MA), and 3-epi-maslinic acid (3-epiMA) were evaluated for their effects on epidermal cell signaling, proliferation, and skin inflammation in relation to their ability to inhibit skin tumor promotion by 12-O-tetradecanoylphorbol-13-acetate (TPA) and compared to UA as the prototype compound. All compounds were given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 64 publications
(85 reference statements)
0
12
0
1
Order By: Relevance
“…Betulinic acid, caffeic acid phenylethyl ester, genistein, palmatine chloride, shikonin and RES were purchased from CaymanChemicals (Ann Arbor, MI, USA), whereas >98% pure corosolic acid, epi-maslinic acid, epi-UA, epi-corosolic and maslinic acid were prepared as recently described. 58 , 59 For all screens, cells in exponential proliferation were seeded in 384-well plates using a Viaflo Assist micro-plate dispenser (Integra Biosciences, Hudson, NH, USA) and allowed to adhere overnight. During the primary screening, HMVP2 cells were screened with the individual NCL compounds at 3 time-points (12, 24 or 48 h) and three doses (5, 10, 20 µM final concentration).…”
Section: Methodsmentioning
confidence: 99%
“…Betulinic acid, caffeic acid phenylethyl ester, genistein, palmatine chloride, shikonin and RES were purchased from CaymanChemicals (Ann Arbor, MI, USA), whereas >98% pure corosolic acid, epi-maslinic acid, epi-UA, epi-corosolic and maslinic acid were prepared as recently described. 58 , 59 For all screens, cells in exponential proliferation were seeded in 384-well plates using a Viaflo Assist micro-plate dispenser (Integra Biosciences, Hudson, NH, USA) and allowed to adhere overnight. During the primary screening, HMVP2 cells were screened with the individual NCL compounds at 3 time-points (12, 24 or 48 h) and three doses (5, 10, 20 µM final concentration).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, UA and Curc both reduced mRNA levels of Cox‐2, a transcriptional target of NF‐κB. Using a higher dose of 2 μmol, we previously reported that UA inhibited TPA‐induced upregluation of Cox‐2 protein levels, and others have shown that Curc also inhibits TPA‐induced protein levels of Cox‐2 . Thus, the greater effects of the combination of UA + Curc on this signaling pathway likely contributed to the greater effects seen on tumor promotion as well as on inflammatory gene expression.…”
Section: Discussionmentioning
confidence: 94%
“…B, Quantitation of Western blots (mean ± SEM; average of at least three independent experiments). *, Significant when compared to TPA group; †, Significant when compared to UA + TPA; #, Significant when compared to Curc + TPA; (P ≤ 0.05, Mann-Whitney U test) we previously reported that UA inhibited TPA-induced upregluation of Cox-2 protein levels, and others have shown that Curc also inhibits TPA-induced protein levels of Cox-2 8. 22 Thus, the greater effects of the combination of UA + Curc on this signaling pathway likely contributed to the greater effects seen on tumor promotion as well as on inflammatory gene expression.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Recent studies from our laboratories using an in vivo model of skin tumor promotion have shown that UA and related triterpenes given topically can activate AMPK in the epidermis of mice treated with TPA . AMPK activation correlated with increased phosphorylation of ULK1 (Ser555) suggesting that AMPK activation by UA and related triterpenes may lead to induction of autophagic cell death.…”
Section: Discussionmentioning
confidence: 99%